Zurück in den Alltag - Mütter nach Behandlung ihrer Alkoholabhängigkeit - Gavez, Silvia (Verlag Barbara Budrich, 2017)
What challenges do mothers face after treating alcohol dependence? The study conducted by the Zurich University of Applied Sciences in cooperation with the Forel Clinic focuses on mothers who have undergone in-patient or day-care treatment. The results of the qualitative study provide an insight into the lives of these mothers returning to their everyday lives.